NILAI MULTIKULTURAL DAN KEARIFAN LOKAL : Analisis Pada Pengelolaan Media Online Dinas Komunikasi, Informatika, Persandian dan Statistik Propinsi Sulawesi Tengah - Alffiyaty, Rizqy; Suriady, Israwaty Suriady; Rohmah Wulandari, Dwi (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
This study aims to determine online media management by Central Sulawesi Province's Office of Communication, Information, Encryption and Statistics (DKIPS) in instilling multicultural values ​​and local wisdom. The research method uses a descriptive qualitative approach, with data collection techniques through interviews, observations, and documentation studies involving five informants at the relevant offices. The study results stated that DKIPS, in disseminating information related to multiculturalism and local wisdom, used online media, namely websites and social media (youtube, Instagram, Twitter, and Facebook). The messages contain the same core information, but the packaging is adapted to the media. The considerations are that it is cheap, easy, and has a broader reach. Information dissemination is currently a collaboration between the Provincial Government Public Relations and DKIPS in managing content related to multiculturalism and local wisdom, such as historical profiles, ancient relics, and also the original products of the people of Central Sulawesi Province.